Characterization of dextrin-based hydrogels : rheology, biocompatibility, and degradation - Carvalho, Joana (2010)
A new class of degradable dextrin-based hydrogels (dextrin-HEMA) was developed. The hydroxyethyl methacrylate ester (HEMA) hydroxyl groups were activated with N,N' carbonyldiimidazole (CDI), followed by their coupling to dextrin, yielding a derivatized material that can be polymerized in aqueous solution to form hydrogels. A comparative study of the stability of the dextrin-HEMA hydrogels and dextrin-vinyl acrylate (dextrin-VA, produced in previous work) revealed that only the firsts are effectively hydrolyzed under physiological conditions. A severe mass loss of dextrin-HEMA gels occurs over time, culminating in the complete dissolution of the gels. Rheologic analysis confirmed that physical structuring is less pronounced when dextrin is modified with methacrylate side groups. The biocompatibility results revealed that the dextrin hydrogels have negligible cell toxicity, irrespective of the hydrogel type (HEMA and VA), allowing cell adhesion and proliferation. Gathering the biocompatibility and the ability to tailor the release profiles, we consider dextrin a promising biomaterial for biomedical applications, namely for controlled release.